IVF sonification: making music to the rhythm of life - Savery, Richard; Gilboa, Daniella; Weinberg, Gil (Interacting with computers, 2025)
Abstract This study explores the use of sonification in improving the In Vitro Fertilization (IVF) experience for expectant parents. The authors propose that the sonification of IVF videos, depicting the division of embryonic cells, can aid in enhancing understanding of embryonic development and foster emotional connections with medical imagery. To demonstrate this concept, the authors developed a system for creating emotional music synchronized with IVF videos, using a combination of rule-based methods and a neural network. The system was evaluated through two studies, including an online survey and a semi-structured interview, with participants being shown the sonified IVF videos. Results indicated a strong preference for videos with sonification among expectant mothers and a perceived relationship between the sonification and the video. The study supports previous findings on the trade-off between aesthetics and information conveyed through sonification, and suggests that sonification can improve the overall experience and stimulate curiosity without necessarily imparting new information about the embryos.